2019
DOI: 10.13106/jafeb.2019.vol6.no3.9
|View full text |Cite
|
Sign up to set email alerts
|

Conservative Loan Loss Allowance and Bank Lending

Abstract: The purpose of this study is to investigate the relation between conservative loan loss accounting practice of banks, defined as accounting behavior that increases loan loss allowances against expected credit losses, and bank lending. Furthermore, we specify the macroeconomic conditions reflecting debtors' borrowing environments and analyze how these conditions affect the relation between conservative loan loss allowances and bank lending. Although existing literature reports that accounting conservatism has a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…As the economy expands, the demand for bank loans increases (Takasu and Nakano, 2020). The growth of the gross domestic product (GDP) had been found to be consistently significant in affecting NPLs (Mustafa and Ali, 2019).…”
Section: Review Of Literaturementioning
confidence: 99%
“…As the economy expands, the demand for bank loans increases (Takasu and Nakano, 2020). The growth of the gross domestic product (GDP) had been found to be consistently significant in affecting NPLs (Mustafa and Ali, 2019).…”
Section: Review Of Literaturementioning
confidence: 99%
“…Bank risk also depends significantly on the business cycle (Bikker & Metzemakers, 2005;Takasu & Nakano, 2019). The existing literature, which focuses on either the effect of business cycle on lending, bank capital and on bank stability or cyclical behavior of bank risk.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Allen et al (2013), Chen and Wu (2014), Choi et al (2013), Fungáčováa et al (2013), Ferri et al (2014) and Gambacorta and Marques-Ibanez (2003) found a significant positive sign between capital and loans Measuring the risk of using Loan Loss Provision. Loan loss provisions can be an important prudential instrument for emerging countries because they play a role in the banking system, especially financial intermediation (Saurina, 2009;Bouvatier & Lepetit, 2012;Takasu & Nakano, 2019). Jiménez and Saurina (2006) show that there is a direct relationship between credit growth and credit risk, so that the rapid increase in loan portfolio is positively associated with an increase in the ratio of non-performing loans in the future.…”
Section: Bank Specific Determinantsmentioning
confidence: 99%